Planktonic availability and settlement of Carcinus maenas megalopae at high temporal resolution in the lower Mira Estuary (SW Portugal) - Amaral, V. (2013)
The current conceptual model of reinvasion and settlement for estuarine brachyuran crabs in mesotidal systems is that megalopae undergo selective tidal stream transport, in an upstream direction, and settle by the end of the flood tide. Recent studies on recruitment processes of Carcinus maenas (L.) have reported a clear decoupling between supply, as larval influx, and settlement events in the lower Mira Estuary (SW Portugal). We investigated, at high temporal resolution, whether overestimation of planktonic abundances and/or deviations of megalopal responses from the conceptual model were responsible for such decoupling. Daily settlement of megalopae was analyzed using regression and spectral analyses to identify periodicities and correlated with tidal amplitude. Hydrological parameters and supply, net flux and hourly concentration of megalopae in the plankton were addressed as factors influencing short, intermediate and long-term settlement, through 50 h sampling series. Supply and surface net flux levels of megalopae were similar and clearly decoupled from settlement on bottom-deployed collectors. Both hourly planktonic concentration and settlement patterns of megalopae fitted the conceptual model at high temporal resolution, with some deviations in terms of light intensity influences. Furthermore, our results suggest that processes preventing settlement and capable of overriding the influence of light intensities—such as turbulence—may explain the decoupling between supply and settlement of shore crab megalopae in the lower Mira Estuary.